Cannabidiol promotes fin regeneration and reduces apoptosis in zebrafish embryos. (November 2021) - Xu, Shisan; Zhang, Huan; Li, Cun-Zhao; Lai, Ping-Shan; Wang, Guijiang; Chan, Yu Suen; Cheng, Shuk Han; Chen, Xueping
Graphical abstract: Highlights: Crude cannabidiol (CBD) extract promoted zebrafish fin regeneration and reduced apoptosis after amputation. 0.625 mg/L pure CBD chemical recapitulated the regenerative action of crude CBD extract, but 2.5 mg/L CBD didn't exhibit pro-regenerative action. CBD inhibited neutrophil accumulation in the wound aera. CBD reduced the number of cell death and downregulated the expression of IL-1β, Caspase 3, and PARP. Abstract: Cannabidiol (CBD) extracts have gained attention for their therapeutic efficacy. The present study used a zebrafish embryo caudal fin amputation model and found 1.25 mg/L crude CBD extract accelerated caudal fin regeneration and reduced apoptosis after amputation, while not altering mitotic regenerating cells. The purity of the CBD extract was 55.5 ± 0.37%. Pure CBD promoted fin regeneration and inhibited neutrophil accumulation in a dose-dependent manner, while these effects were not seen in a high concentration of CBD (2.5 mg/L), possibly due to the toxicity of the high dose. An equivalent amount of pure CBD (0.625 to 1.25 mg/L) enhanced regeneration and reduced apoptosis similarly to crude CBD extract (1.25 mg/L). Additionally, CBD reduced the gene expression level of cxcl8, tnf-a, and il-1β, and protein expression level of IL-1β, Caspase 3, and PARP, but not Bcl-2 or Bax. These results suggest that CBD exerts its effect on wound pro-regeneration in part by modulating the inflammatory response and the IL-1β/Caspase 3/PARP signal pathway.